Teaching English as a Second Language at a University in Colombia That Uses Virtual Environments: A Case Study - Sandra Vega-Carrero; Manuel Pulido; Nancy Esther Ruiz-Gallego (Revista Electrónica Educare)
This article presents the results of a research study conducted with college students at a University in Colombia that offers an online program of English as a Foreign Language. The goal of this study was to understand the students’ perceptions. It mainly responded to the following research questions: Why do these students participate in an EFL online program? What are their perspectives about the methodology used in the virtual environment to learn a second language? What are their perspectives about the environmental factors involved in the learning process? And how are technical factors influencing the online learning process? This study used a qualitative research method. A questionnaire-based survey method was used for data collection. The population participating in this research was selected randomly, and the participants were promised anonymity prior to the completion of the questionnaire. It was found that online students master technology while learning in a virtual environment. In addition, students perceived that, with the activities promoted in the e-learning environments, they increased their vocabulary skills. Also their grammar and reading skills tended to improve considerably. However, students perceived that the interaction between them and their instructors should increase, so they would have the possibility of answering their questions and strengthening their speaking and writing skills.